Psychological Counseling Service “Together” at University of Genoa: Students’ Psychological Profile in Pre and Post Pandemic - Pace, Cecilia Serena; Usai, Maria Carmen; Bizzi, Fabiola; Minetto, Patrizia; Alcetti, Alberta; Zanobini, Mirella (Frontiers in Psychology, 2022)
The present explorative study aims to analyse the profiles of students seeking help in the two areas (emotion/relation or learning areas) of a psychological counseling service for students at the University of Genoa to better understand their request for support in pre- and post-pandemic periods. A total of 229 university students seeking for help from November 2018 to December 2021 completed a psychological battery investigating emotion regulation difficulties and pathological domains of personality (students taken in charge by the emotion/relation area) or motivation issues and anxiety and resilience levels (students taken in charge by the learning area). Regarding the emotion/relation area, results show that problems in emotion dysregulation, and especially in regulating positive emotions, are associated to several pathological domains of personality, such as Psychoticism, Antagonism, Disinhibition, Detachment, and Negative Affectivity. Among the learning area, motivational aspects concerning confidence in one’s intelligence, academic self-efficacy, and learning goals are differently associated with anxiety and resilience above and beyond other aspects, such as attributions. Some limited but significant differences emerge from the comparison between pre- and post-COVID periods: a reduction in detachment in students attending the emotion/relation area, an increase of students with high levels of anxiety in the learning area. These results support the importance of continually operating on emotional and motivational aspects to enhance the students’ well-being and therefore sustaining thus their academic careers.